2012
DOI: 10.1093/nar/gks1095
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase beta controls replication factor C assembly and function

Abstract: Genomic integrity is preserved by the action of protein complexes that control DNA homeostasis. These include the sliding clamps, trimeric protein rings that are arranged around DNA by clamp loaders. Replication factor C (RFC) is the clamp loader for proliferating cell nuclear antigen, which acts on DNA replication. Other processes that require mobile contact of proteins with DNA use alternative RFC complexes that exchange RFC1 for CTF18 or RAD17. Phosphoinositide 3-kinases (PI3K) are lipid kinases that genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(78 reference statements)
1
6
0
Order By: Relevance
“…Elg1 might also be required for the recruitment of chromatin-associated proteins to the replication factory for the construction of the chromatin architecture as chromosome duplication proceeds. A previous report showed that Elg1 physically and genetically interacts with Rad27 (FEN1) (Kanellis et al 2003), and RFC1 and Ctf18 also interact with various proteins other than PCNA (Levin et al 2004;Franco et al 2005;Shiomi et al 2007;Farina et al 2008;Redondo-Munoz et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Elg1 might also be required for the recruitment of chromatin-associated proteins to the replication factory for the construction of the chromatin architecture as chromosome duplication proceeds. A previous report showed that Elg1 physically and genetically interacts with Rad27 (FEN1) (Kanellis et al 2003), and RFC1 and Ctf18 also interact with various proteins other than PCNA (Levin et al 2004;Franco et al 2005;Shiomi et al 2007;Farina et al 2008;Redondo-Munoz et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…PCNA requires the ATPase activity of the clamp loader, replication factor C (RFC), to open and encircle double-stranded DNA (Indiani and O'Donnell, 2006 ). Through a kinase-independent function, p110β was found to interact with RFC1, a subunit of the RFC complex, and thereby promote loading of PCNA onto chromatin (Redondo-Muñoz et al, 2013 ). It is interesting to note that p110β regulates PCNA loading through both kinase-dependent and -independent activities as phosphorylation of the cell cycle inhibitor p21 Cip1 on T145 releases PCNA from its suppressive binding to p21 Cip1 (Marqués et al, 2009 ).…”
Section: Dna Replication and Damage Repairmentioning
confidence: 99%
“…It is interesting to note that p110β regulates PCNA loading through both kinase-dependent and -independent activities as phosphorylation of the cell cycle inhibitor p21 Cip1 on T145 releases PCNA from its suppressive binding to p21 Cip1 (Marqués et al, 2009 ). Depletion of p110β with RNA interference (RNAi) increased the expression levels of p21 Cip1 and its association with PCNA, and impaired PCNA-RFC association and loading onto chromatin (Marqués et al, 2009 ; Redondo-Muñoz et al, 2013 ). The interaction of PCNA and p21 Cip1 , occurring through the same domain as the PCNA-DNA pol δ interaction, negatively regulates S-phase progression (Cazzalini et al, 2003 ).…”
Section: Dna Replication and Damage Repairmentioning
confidence: 99%
“…Furthermore, both the activity and scaffolding functions of P110β also facilitate DNA repair after DNA damage induced by ionizing radiation. NBN is a critical sensor of DNA damage, localizes to DNA damage‐induced foci, and is required for recruitment of protein complexes that affect DNA repair . NBN interacts with p110 β, and NBN localization at DNA damage‐induced foci is severely reduced when p110β is depleted.…”
Section: Ppin Function Within the Nucleusmentioning
confidence: 99%